Laboratornĕ potvrzené prípady hemoragické horecky s ledvinovým syndromem v letech 1989-1990 na Breclavsku - Kobzík, J; Danes, L (Ceskoslovenska epidemiologie, mikrobiologie, imunologie, 1992)
The authors describe the first three cases with a serologically confirmed hantaviral aetiology in the Czech Republic. It is the causal agent of haemorrhagic fever with renal syndrome, western type (strain CG 18-20, identical with the Puumala prototype). All patients come from a locality where since 1984 very actively a natural focus of hantaviral infection was investigated in small mammals, and where formerly groups of farmers were found with a high herd immunity with hantavirus. The disease was present in a mild to medium severe form with some sequelae. In the discussion the authors draw attention to the necessity of wider use of aetiological diagnosis in suspect diseases.
Keywords: hemoragická horečka s renálním syndromem; Czechoslovakia; Hemorrhagic Fever with Renal Syndrome; Male; protilátky virové; Fluorescent Antibody Technique; Orthohantavirus; fluorescenční protilátková technika; Adult; dospělí; mužské pohlaví; lidé; ženské pohlaví; Hantavirus; Humans; Československo; Antibodies, Viral; Female; lidé středního věku; Middle Aged